Can scare tactics and fear-based messages help deter substance misuse: a systematic review of recent (2005–2017) research. (4th May 2019) - Esrick, Josh; Kagan, Raanan G.; Carnevale, John T.; Valenti, Maria; Rots, Gisela; Dash, Kim
Abstract: Introduction: Historically, substance use prevention relied heavily on scare tactics and fear-based messages. However, these messages were discouraged from use due to research finding them ineffective or harmful. This review sought to determine if recent research continues to support this finding. Methods: We conducted a literature review of relevant peer-reviewed studies from 2005 to 2017, categorising results as showing clear evidence of effectiveness, mixed evidence of effectiveness or no evidence of effectiveness. Research on historical scare tactics and fear-based messages was reviewed as a baseline and research on related theoretical models was reviewed for context. Results: We identified 17 studies that met our inclusion criteria: 10 targeting tobacco use, five targeting alcohol use, one targeting marijuana use and one targeting methamphetamine use. Eight (8) studies found that these messages were more effective at influencing substance use-related measures than positive emotion prevention messages or control messages. Five (5) studies found mixed evidence, and four (4) studies found no evidence of effectiveness. Discussion: Though not conclusive, our results suggest that these messages may be more effective than previously shown. However, many of the studied messages differed in tone and content from similar, historical messages. Organizations interested in implementing these messages should note these differences.